(untitled) (Journal of the Professional Association for Cactus Development, 2003)
Several species of hemiepiphytic vine cacti have recently been introduced to Israel as fruit crops. As part of the domestication process, these species must be evaluated for their response to environmental conditions. Differences in tolerance to low and high field temperatures were noticed between species. In vitro viability tests followed by field observations were conducted in an effort to find a rapid and reliable method for predicting response to high and low temperatures. Neutral-red and 2,3,5-triphenyltetrazolium chloride (TTC) tests were found to be appropriate for monitoring high temperature stress, but proved inadequate for evaluating response to low temperatures.